2009
DOI: 10.1111/j.1747-0765.2009.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrification inhibition byBrachiaria humidicolaroots varies with soil type and inhibits nitrifying bacteria, but not other major soil microorganisms

Abstract: The tropical pasture grass Brachiaria humidiola (Rendle) Schweick releases nitrification inhibitory compounds from its roots, a phenomenon termed ‘biological nitrification inhibition’ (BNI). We investigated the influence of root exudates of B. humidicola on nitrification, major soil microorganisms and plant growth promoting microorganisms using two contrasting soil types, Andosol and Cambisol. The addition of root exudates (containing BNI activity that is expressed in Allylthiourea unit (ATU) was standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 33 publications
1
52
1
Order By: Relevance
“…Using hydroponic systems, it was claimed that the exudation of BNI substances from roots of Bh is an active release of biological nitrification inhibitors that are triggered by the presence of NH 4 + (Subbarao et al 2007b). These Bh exudates contained BNI active substances like methyl-p-coumarate and methyl ferulate, while the shoot tissue contained other very effective BNI substances such as linoleic acid (LA) and linolenic (LN) acid (Gopalakrishnan et al 2009). Additionally, the cyclic diterpene brachialactone was suggested to be the main substance in root exudates of Bh that suppresses nitrification ).…”
Section: Introductionmentioning
confidence: 99%
“…Using hydroponic systems, it was claimed that the exudation of BNI substances from roots of Bh is an active release of biological nitrification inhibitors that are triggered by the presence of NH 4 + (Subbarao et al 2007b). These Bh exudates contained BNI active substances like methyl-p-coumarate and methyl ferulate, while the shoot tissue contained other very effective BNI substances such as linoleic acid (LA) and linolenic (LN) acid (Gopalakrishnan et al 2009). Additionally, the cyclic diterpene brachialactone was suggested to be the main substance in root exudates of Bh that suppresses nitrification ).…”
Section: Introductionmentioning
confidence: 99%
“…Subbarao et al (2009) were able to isolate an effective nitrification inhibitor (brachialactone) from the root exudates of B. humidicola. Gopalakrishnan et al, (2009) also reported a 29 % reduction in nitrification with an application of 182 mg (NH 4 ) 2 SO 4 -N kg −1 of soil associated with the application of exudates of B. humidicola.…”
Section: Discussionmentioning
confidence: 90%
“…Root extracts were obtained according to the methodology described by Gopalakrishnan et al, (2009), in which 400 grams of fresh roots of Brachiaria humidicola or Sacharrum spontaneum were washed in running water, set in a container, slightly macerated using a spatula and placed in 2 L of distilled water for 36 h under 20 ºC to transfer the extracts to the solution. Polar metabolites were extracted from 100 µL of root extracts of Brachiaria humidicola and Sacharrum spontaneum, using the methodology described by Giavalisco et al, (2011).…”
Section: Characterization and Experimental Designmentioning
confidence: 99%
“…BNIs) released from the roots must be stable in the soil environment for several weeks. This was confirmed by adding BNIs to the soil along with NH 4 + as the N source to determine their inhibitory effects on soil nitrification over a 60 d period (Subbarao et al 2006b, Gopalakrishnan et al 2009). …”
Section: Stability Of Bnis In Soil Systemsmentioning
confidence: 98%